2022
DOI: 10.1155/2022/1035475
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Standardized Brazilian Green Propolis Extract (EPP-AF®) on Inflammation in Haemodialysis Patients: A Clinical Trial

Abstract: Background. Patients on haemodialysis (HD) present a significant inflammatory status, which has a pronounced negative impact on their outcomes. Propolis is a natural resin with anti-inflammatory and immunomodulatory properties. We assessed the safety and impact of a standardized Brazilian green propolis extract (EPP-AF®) on the inflammatory status in patients under conventional HD. Methods. Patients were assigned to receive 200 mg/day of EPP-AF® for 4 weeks followed by 4 weeks without the drug, and changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The safety analysis was performed throughout the entire study period. Previous randomized studies that used EPP-AF had already shown the safety profile of this medication, even in patients with chronic kidney disease undergoing hemodialysis 11 , 17 , 26 . Although shock and MV were on the list of severe adverse events, we cannot link the occurrence of such events to the drug tested due to the severity of the disease or even secondary infections in every patient who had them, especially because it has happened in both groups tested.…”
Section: Discussionmentioning
confidence: 99%
“…The safety analysis was performed throughout the entire study period. Previous randomized studies that used EPP-AF had already shown the safety profile of this medication, even in patients with chronic kidney disease undergoing hemodialysis 11 , 17 , 26 . Although shock and MV were on the list of severe adverse events, we cannot link the occurrence of such events to the drug tested due to the severity of the disease or even secondary infections in every patient who had them, especially because it has happened in both groups tested.…”
Section: Discussionmentioning
confidence: 99%
“…Attention is drawn to the imperative of standardizing this bee-derived product while implementing rigorous quality control measures. Certain researchers have already taken steps in this direction, particularly in relation to Brazilian green propolis [ 315 ] and propolis of the poplar variety [ 316 , 317 , 318 ]. It is only when such standardization is achieved that this natural product can truly serve as a viable adjunctive therapy with internationally recognized quality control standards.…”
Section: Shortcomings and Perspectivesmentioning
confidence: 99%
“…For instance, in a population with chronic kidney disease undergoing hemodialysis, the use of propolis for four weeks led to significant reductions in the levels of TNF-alpha, gamma interferon, IL-1, and other cytokines [ 45 ]. Additionally, a randomized study involving patients hospitalized with COVID-19 revealed that those who received daily doses of 400 to 800 mg of propolis for seven days had a shorter hospital stay compared to those who received placebo [ 46 ].…”
Section: Future Perspectivesmentioning
confidence: 99%